Image Reconstruction Algorithm Based on Tree Sparsity Model for Visual Sensor Network - Min Hu; Xuwei Huang; Dan Long; Cailiang Shen (Dianxin kexue)
A tree sparsity mode1 based image compressed sensing（CS）algorithm was proposed to efficiently explore the correlation in visua1 sensor networks（VSN）data. Based on the analysis of wavelet sparsity，a tree sparsity mode1 for VSN image was established and a new CS recovery algorithm for this mode1 was proposed. Analysis and experimenta1 results demonstrate that the proposed algorithm can significantly reduce the measurement for the accurate recovery，and subsequently 1ower energy consumption of data traffic in VSN.